(untitled) (Journal of Engineering, 2024)
As cooling air using water injection was limited by a range of humidity ratio so indirect humidification for air consider, this research take the study of heat transfer through a perpendicular plate heat exchanger to discover the influence optimum conditions on dehumidification efficiency and the amount of heat transfer energy across the plates of heat exchanger so calculating dehumidification efficiency and the amount of heat transfer energy across the plates of heat exchanger depending on the change of primary and secondary air flow rate using an experimental apparatus with an instruments for measuring air flow rate dry bulb temperature and wet bulb temperature on air entry and exit sections, experimental procedure by fixing primary air mass flow rate with changing secondary air mass flow rate once and the condition of entering primary air another time, also fixing secondary air mass flow rate with primary air mass flow rate once and the condition of entering primary ait another time Results show that the increasing of both the dehumidification efficiency and the amount of heat transfer energy across the plates of heat exchanger depend on the increasing of secondary and decreasing of primary air flow rate, percentage of increasing dehumidification efficiency 16 when secondary air mass flow rate increase from 0 to 0.2 kg’s and percentage of increasing heat transfer 35 with above flow rate, percentage of decreasing dehumidification efficiency 12 when primary air mass flow rate increasing percentage 12 and percentage of increasing heat transfer 21 with above flow rate.